IGA Antibody Induced by Immunization With Pneumococcal Polysaccharides Is a Prognostic Tool in Common Variable Immune Deficiencies - Pulvirenti, Federica; Milito, Cinzia; Cavaliere, Filomena Monica; Mezzaroma, Ivano; Cinetto, Francesco; Quinti, Isabella (Frontiers in Immunology, 2020)
The evaluation of the response to vaccination in patients with inborn errors of immunity is a tool to evaluate T-dependent and T-independent antibody residual function of B lymphocytes and it is part of the diagnostic definition for Common Variable Immune Deficiencies. Currently used classifications for Common Variable Immune Deficiencies patients are based on the frequency of B cell subsets, and have been proven as a valid instrument for identification of patients at higher risk of infectious and non-infectious complications. This six-years period observational study delineated the measurement of specific IgA antibodies induced by a 23-valent pneumococcal polysaccharides vaccine by a standardized ELISA for the quantification of IgA antibodies to all 23 pneumococcal serotypes as an additional prognostic marker in 74 CVID patients. The inability to mount an IgA-mediated response against the pneumococcal polysaccharide antigens or the inability to maintain the antibody response over time identified poor IgA CVID responders with severe immunological impairment, great risk of co-morbidities, and poor prognosis. The division of CVID patient into specific IgA-non responders and IgA-responders discriminated better than other CVID classifications for infectious risk, while it overlapped for non-infectious complications. Our study suggested to add the evaluation of the antibody response by the 23-valent IgA assay in the clinical monitoring of CVID patients.